Applying options to evaluate service innovations in the automotive industry. (7th July 2005) - Lu, Iuan-Yuan; Lin, Liang-Hung; Wu, Guo-Chiang
The service sector is important in the economy of most advanced countries. Focusing on service innovation, this study examines customer service activities in the automobile industry from 2001 to 2003, and identifies the most representative and innovative services of motor firms. These service innovations are not recommended under traditional discounted cash flow (DCF) assessment. However, a positive options-based net present value (NPV) motivates companies to innovate their service activities and thereby increase the number of products they sell. Evidence shows that an options-based evaluation is more suitable than traditional approaches. The results of this study should help managers to address and evaluate service innovations.